Language of globalized media as a hate generator on the Balkans - Kostadinović, Maja R. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The Language of hatred in its basic war inciting sense has almost disappeared from media. However, its mutants still may come out into public though intolerance or political settlements. There is no community insensitive to some kinds of hatred. Neither developed democratic nor, even less communities in new Balkan states. Members of minority groups are specially under impact – from ethnic via religious to those specially vulnerable community groups such as handicapped, with specific diseases and juveniles and alike. This paper is about that tolerance and hatred which still exists in media on Balkan. The writer points to the relationship of journalists to those minority groups and offers some of possible ways for improving the relationship between them.